122k views
4 votes
2/3(9+12x) = 4(2x - 3/4)

User JBrooks
by
6.2k points

1 Answer

2 votes

For this case we must solve the following equation:


\frac {2} {3} (9 + 12x) = 4 (2x- \frac {3} {4})

We apply distributive property to both sides of the equation:


\frac {2 * 9} {3} + \frac {2 * 12x} {3} = 4 * 2x- \frac {4 * 3} {4}

We simplify:


\frac {18} {3} + \frac {24x} {3} = 8x- \frac {12} {4}

Subtracting 8x from both sides of the equation:


6 + 8x = 8x-3\\6 = -3

Equality is not met, there are no "x" values that make the equation true.

ANswer:

The equation has no solution

User Jeff Hogg
by
5.8k points